Performance assessment of disc spring-based self-centering braces for seismic hazard mitigation. (1st September 2021) - Wang, Wei; Fang, Cheng; Shen, Deyang; Zhang, Ruibin; Ding, Jiemin; Wu, Honglei
Highlights: A novel disc spring-based self-centering damper is presented. Experimental study on six full-scale damper specimens is conducted. Analytical expressions are developed and validated through comparisons against test results. System level analysis is conducted considering various brace parameters. Design recommendations are given following the system level analysis. Abstract: A novel type of self-centering bracing system employing a disc spring-based damper is presented in this study. The proposed damper employs a special detailing which enables fast assembly and reliable mechanical performance, and has high flexibilities in load resistance, deformability and energy dissipation capacity, catering to various design objectives. The working principle of the damper is first introduced, followed by a comprehensive experimental study on six full-scale damper specimens subjected to different loading protocols. The specimens exhibit very stable flag-shaped hysteretic behavior and are fully reusable with almost no damage after experiencing the considered test sequence. Reliable energy dissipation is provided by the dampers with little sensitivity to the repeated cyclic loading, where a typical equivalent viscous damping of 20% is achieved at large deformations. The work is then extended to a system level analysis, considering varying brace parameters, to evaluate the effectiveness of the self-centering bracing system in seismic control. A buckling-restrained braced frame is also included in the analysis for comparison. Among other findings, the study indicates that the fullness of the flag-shaped hysteresis is a critical factor affecting the key structural performances. In particular, decreasing the energy dissipation factor is effective in eliminating the residual deformation, but at the cost of amplified peak deformation and floor acceleration responses. A "partial self-centering" system, which allows certain static residual deformation of the brace, is found to simultaneously suppress the peak deformation, residual deformation, and peak floor acceleration.